Spectroscopic Investigations of Porphyrin-TiO2 Nanoparticles Complexes - Andra Dinache; Simona Nistorescu; Tatiana Tozar; Adriana Smarandache; Mihai Boni; Petronela Prepelita; Angela Staicu (Molecules, 2022)
This study presents the spectral characterization of TiO2 nanoparticles (NPs) functionalized with three porphyrin derivatives: 5,10,15,20-(Tetra-4-aminophenyl) porphyrin (TAPP), 5,10,15,20-(Tetra-4-methoxyphenyl) porphyrin (TMPP), and 5,10,15,20-(Tetra-4-carboxyphenyl) porphyrin (TCPP). UV-Vis absorption and Fourier transform infrared spectroscopy–attenuated total reflection (FTIR-ATR) spectroscopic studies of these porphyrins and their complexes with TiO2 NPs were performed. In addition, the efficiency of singlet oxygen generation, the key species in photodynamic therapy, was investigated. UV-Vis absorption spectra of the NPs complexes showed the characteristic bands of porphyrins. These allowed us to determine the loaded porphyrins on TiO2 NPs functionalized with porphyrins. FTIR-ATR revealed the formation of porphyrin-TiO2 complexes, suggesting that porphyrin adsorption on TiO2 may involve the pyrroles in the porphyrin ring, or the radicals of the porphyrin derivative. The quantum yield for singlet oxygen generation by the studied porphyrin complexes with TiO2 was higher compared to bare porphyrins for TAPP and TMPP, while for the TCPP-TiO2 NPs complex, a decrease was observed, but still maintained a good efficiency. The TiO2 NPs conjugates can be promising candidates to be tested in photodynamic therapy in vitro assays.